2018
DOI: 10.1021/acs.est.8b03180
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Glycoproteins Isolated from Extracellular Polymeric Substances of Full-Scale Anammox Granular Sludge

Abstract: ANaerobic AMMonium OXidation (anammox) is an established process for efficient nitrogen removal from wastewater, relying on anammox bacteria to form stable biofilms or granules. To understand the formation, structure, and stability of anammox granules, it is important to determine the composition of the extracellular polymeric substances (EPS). The aim of this research was to elucidate the nature of the proteins, which are the major fraction of the EPS and were suspected to be glycosylated. EPS were extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(63 citation statements)
references
References 53 publications
1
62
0
Order By: Relevance
“…Proteins have recently been suggested to play a structural role in anammox community extracellular polymeric substances (EPS) ( 8 ), particularly cross β-sheet proteins, O-glycosylated glycoproteins ( 9 ) and possibly even amyloids ( 10 ). Nonetheless, no direct functional characterization has been undertaken on a known or isolated anammox biofilm extracellular protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins have recently been suggested to play a structural role in anammox community extracellular polymeric substances (EPS) ( 8 ), particularly cross β-sheet proteins, O-glycosylated glycoproteins ( 9 ) and possibly even amyloids ( 10 ). Nonetheless, no direct functional characterization has been undertaken on a known or isolated anammox biofilm extracellular protein.…”
Section: Introductionmentioning
confidence: 99%
“…We identified the glycoprotein Brosi_A1236 as the most abundant protein in the "Ca. Brocadia sinica"-enriched biofilm extracellular extract (12), which belongs to the class of glycoproteins extracted from other anammox sludges, including Kustd1514 from "Candidatus Kuenenia stuttgartiensis"-enriched sludge and its homolog from "Candidatus Brocadia sapporoensis"-enriched sludge (9,13). These are a class of anammox proteins similar to the heme C proteins that perform common reactions in anammox metabolism (e.g., hydrazine synthase).…”
mentioning
confidence: 99%
“…12 Previous studies indicate that there are abundant polysaccharides, hydrophobic amino acids and proteins in the EPS of anammox granular sludge. 13,14 Conceivably, the EPS of anammox biomass may be a good source of the CQDs. Currently, there are no studies reported on applying anammox-based EPS to synthesize CQDs for quantication of heavy metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the available studies focused on the determination of the amount and stratification structure of PS and PN in activated sludge [9][10][11][12]. Furthermore, numerous PN have been identified by using LC-MS and MALDI-MS in EPS [13][14][15]. However, PS have not been thoroughly elucidated yet, due to their strong hydrophilicity and component complexity.…”
Section: Introductionmentioning
confidence: 99%